Whole-Genome Phylogenetic Analysis of Influenza B/Phuket/3073/2013-Like Viruses and Unique Reassortants Detected in Malaysia between 2012 and 2014 - Oong, X.Y.; Ng, K.T.; Tan, J.L.; Chan, Kok Gan; Kamarulzaman, Adeeba; Chan, Yoke Fun; Sam, I-Ching; Tee, Kok Keng (Public Library of Science, 2017)
Reassortment of genetic segments between and within influenza B lineages (Victoria and Yamagata) has been shown to generate novel reassortants with unique genetic characteristics. Based on hemagglutinin (HA) and neuraminidase (NA) genes, recent surveillance study has identified reassortment properties in B/Phuket/3073/2013-like virus, which is currently used in the WHO-recommended influenza vaccine. To understand the potential reassortment patterns for all gene segments, four B/Phuket/3073/2013-like viruses and two unique reassortants (one each from Yamagata and Victoria) detected in Malaysia from 2012-2014 were subjected to whole-genome sequencing. Each gene was phylogenetically classified into lineages, clades and sub-clades. Three B/Phuket/3073/2013-like viruses from Yamagata lineage were found to be intra-clade reassortants, possessing PA and NA genes derived from Stockholm/12-like sub-clade, while the remaining genes from Wisconsin/ 01-like sub-clade (both sub-clades were within Yamagata Clade 3/Yam-3). However, the other B/Phuket/3073/2013-like virus had NS gene that derived from Stockholm/12-like sub-clade instead of Wisconsin/01-like sub-clade. One inter-clade reassortant had Yamagata Clade 2/Yam-2-derived HA and NP, and its remaining genes were Yam-3-derived. Within Victoria Clade 1/Vic-1 in Victoria lineage, one virus had intra-clade reassortment properties: HA and PB2 from Vic-1B sub-clade, MP and NS from a unique sub-clade "Vic- 1C", and the remaining genes from Vic-1A sub-clade. Although random reassortment event may generate unique reassortants, detailed phylogenetic classification of gene segments showed possible genetic linkage between PA and NA genes in B/Phuket/3073/2013-like viruses, which requires further investigation. Understanding on reassortment patterns in influenza B evolution may contribute to future vaccine design.